Research Integrity in Europe and Greece - Χαριτίδης (Constantinos Charitidis) Κωνσταντίνος; Κούμουλος (Elias Koumoulos) Ηλίας; Κάβουρας (Panagiotis Kavouras) Παναγιώτης; Κρητικός (Michalis Kritikos) Μιχάλης; Γκαράνη-Παπαδάτου (Tina Garani-Papadatos) Τίνα (Bioethica, 2016)
Research integrity is an essential and integral part of scientific research ethics. It is commonly accepted that the value of scientific research vitally depends on the fulfillment of research integrity codes of conduct. The unbreakable linkage (relation) between research value and research integrity does not reflect only its attachment to the application of proper scientific method but also its acceptance from the society. In this work we present a survey on the organization of the institutions of research integrity in international, European and national level. Emphasis is given in the description of the present state in Greece in the level of Higher Educational Institutes, Research Centers and Committees. Also, we focus on the actions taken from National Technical University of Athens, as well as the initiative from EARTHnet network and their efforts for institutionalization of a common code of conduct in scientific research at a national level.